Development of Google Classroom-Based Learning Media for Strengthening Premarital Education from a Pancasila Education Perspective among Grade XI Social Humanities Students at MA Al-Fattahiyyah - Ri’ayatus Solihah; Nurna Listya Purnamasari (Darul Yasin Al Sys, 2026)
Pancasila Education learning at MA Al-Fattahiyyah remains largely dependent on conventional instructional approaches, resulting in the limited integration of digital media into premarital education materials. This condition reduces learning interactivity and restricts student engagement in the instructional process. This study aimed to develop Google Classroom-based learning media to strengthen premarital education from the perspective of Pancasila Education and to evaluate its validity and feasibility. The study employed a Research and Development approach using the ADDIE model, comprising the Analysis, Design, Development, Implementation, and Evaluation stages. The participants included a media expert, a subject-matter expert, and Grade XI Social Humanities students at MA Al-Fattahiyyah. Data were collected through observation, interviews, questionnaires, and documentation and were analyzed using descriptive quantitative and qualitative techniques. The findings showed that the media expert validation score reached 93.75%, the subject-matter expert validation score reached 93.75%, the small-group trial achieved 94.5%, and the large-group trial obtained 93.8%, resulting in an overall average score of 93.95%, which was categorized as highly valid. The study concludes that the developed Google Classroom-based learning media is feasible for instructional implementation in Pancasila Education. These findings contribute to the development of digital learning media for premarital education and imply that Google Classroom can enhance instructional quality, learning motivation, and students’ understanding of premarital education materials.